IDENTIFIKASI DAN PENETAPAN KADAR ASAM BENZOAT PADA KECAP ASIN YANG BEREDAR DI KOTA MANADO - Sumarauw, Windy; Fatimawali, Fatimawali; Yudistira, Adithya (PHARMACON, 2013)
ABSTRACT Â The salty ketchup is one of the food additives commonly added to food. The purpose of this study was to identily and determine levels of use of benzoic acid compound as a preservative in salty ketchup turn in Manado. The samples used were four different ketchup brands produced locally in Manado. Sample identification is done by extracting the sample using diethyl ether solvent. Ether was evaporated to obtain dried ketchup extract. The extracted residue was reacted with 5 % FeCl3 resulting in brown precipitate which proves that it contains benzoic acid. Determination of the preservative (benzoic acid) was determined using UV-Vis spectrophotometer. The results showed that four samples of ketchup used benzoic acid as a preservative. Using preservative not weather threshold set out in Decree PERMENKES RI No 722/MenKes/Per/IX/88. Â Keywords : benzoate, ketchup, Manado, UV-Vis spectrophotometer.